2020
DOI: 10.21203/rs.3.rs-20777/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 on psychology of nurses working in the emergency and fever outpatient:A cross-sectional survey

Abstract: Background COVID-19 poses a great challenge to the global health system. The nurses of emergency and fever outpatient (EFO) act as gatekeepers to the health care system in the public health response to COVID-19 epidemic. This study examined the psychological impact of COVID-19 upon EFO nurses in Chinese hospitals. Methods In midmonth of February, 2020, convenience sampling was used to recruit EFO nurses from hospitals in Jiangsu Province. Data were obtained by self-administered online questionnaires, which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
3
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 41 publications
4
22
3
3
Order By: Relevance
“…The current study revealed that 69.6%, 55.3%, and 20.5% of the respondents experienced anxiety, depression, and stress respectively in response to the COVID-19 pandemic. The prevalence of anxiety in this study was higher than studies conducted in Jiangsu Province; China; 37.9%, 22 China; 46.04, 23 Jinzhong, Shanxi Province, China; 39%, 24 Wuhan china; 24.1%, 25 China; 54.4%, 26 Spain; 58.6%, 27 Jordan; 42.4%, 28 New York; 40%, 29 Singapore; 14.5%, 30 and Guangdong China; 55.4%. 31 The possible justification for this difference might be due to the difference in socioeconomic, cultural, and environmental factors such as attitudes, lack of adequate equipment like personal protective equipment and resources contribute to coping with the psychological crisis of the pandemic.…”
Section: Discussioncontrasting
confidence: 80%
See 4 more Smart Citations
“…The current study revealed that 69.6%, 55.3%, and 20.5% of the respondents experienced anxiety, depression, and stress respectively in response to the COVID-19 pandemic. The prevalence of anxiety in this study was higher than studies conducted in Jiangsu Province; China; 37.9%, 22 China; 46.04, 23 Jinzhong, Shanxi Province, China; 39%, 24 Wuhan china; 24.1%, 25 China; 54.4%, 26 Spain; 58.6%, 27 Jordan; 42.4%, 28 New York; 40%, 29 Singapore; 14.5%, 30 and Guangdong China; 55.4%. 31 The possible justification for this difference might be due to the difference in socioeconomic, cultural, and environmental factors such as attitudes, lack of adequate equipment like personal protective equipment and resources contribute to coping with the psychological crisis of the pandemic.…”
Section: Discussioncontrasting
confidence: 80%
“…The prevalence of stress in this study is consistent with studies conducted in Guangdong, China; 24.7%. 31 However, the finding of this study was lower than studies conducted in Jiangsu Province, China; 32.23%, 22 Jinzhong, Shanxi Province, China; 49.1%, 24 Wuhan, China; 29.8%, 25 multiple centers in China; 28%, 26 Jordan; 50.1%, 28 and New York; 64%. 29 The possible reason for this difference might be due to the difference in the study period in which feelings when the COVID-19 pandemic first appears and overtime may vary.…”
contrasting
confidence: 79%
See 3 more Smart Citations